DECIPHERING THE LANDSCAPE OF CERRO COLORADO (CÓRDOBA, ARGENTINA): THE SPATIAL REMINISCENCIES IN THE POETRY AND THE MELODY OF ATAHUALPA YUPANQUI - Arosteguy, Agustín (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1170, 2021)
This article wishes to explore the landscape of Cerro Colorado and its relationship with the compositions of Atahualpa Yupanqui. Based on the poetic and melodic components of some songs by the singer-songwriter, the aim is to describe the way in which the geographical imaginaries were constructed. In this sense, the elements of nature that Yupanqui used to decipher the landscape are identified. As a methodology, a qualitative approach was used that consisted, on the one hand, in the selection of songs and the qualitative analysis of their content and melody and, on the other, field work was carried out in the town of Cerro Colorado (Argentina), in which participant observation and individual interviews were made. The results confirm that Yupanqui, captured symbolic and conceptual elements that make the configuration of a singular and poetic geographic imagery.